Maximal strength training improves aerobic endurance performance - Hoff, J.; Gran, A.; Helgerud, J. (Scandinavian Journal of Medicine & Science in Sports, 2002)
The aim of this experiment was to examine the effects of maximal strength training with emphasis on neural adaptations on strength- and endurance-performance for endurance trained athletes. Nineteen male cross-country skiers about 19.7 +/- 4.0 years of age and a maximal oxygen uptake (VO2 max) of 69.4 +/- 2.2 mL x kg-1 x min-1 were randomly assigned to a training group (n = 9) or a control group (n = 10). Strength training was performed, three times a week for 8 weeks, using a cable pulley simulating the movements in double poling in cross-country skiing, and consisted of three sets of six repetitions at a workload of 85% of one repetition maximum emphasizing maximal mobilization of force in the concentric movement. One repetition maximum improved significantly from 40.3 +/- 4.5 to 44.3 +/- 4.9 kg. Time to peak force (TPF) was reduced by 50 and 60% on two different submaximal workloads. Endurance performance measured as time to exhaustion (TTE) on a double poling ski ergometer at maximum aerobic velocity, improved from 6.49 to 10.18 min; 20.5% over the control group. Work economy changed significantly from 1.02 +/- 0.14 to 0.74 +/- 0.10 mL x kg-0.67 x min-1. Maximal strength training with emphasis on neural adaptations improves strength, particularly rate of force development, and improves aerobic endurance performance by improved work economy.